A CASE STUDY OF FORMATION DAMAGE MITIGATION ON â€œXâ€ FIELD, SUMATRA - Septi Anggraeni (Scientific Contributions Oil and Gas, 2015)
Formation damage might cause low oil well productivity, therefore it is very important to effectivelyÂ handle this issue. In fact, every operation in the field-drilling, completion, workover, production andÂ stimulation, is a potential source of formation damage. In this case study, the oil company â€œAâ€ plan toÂ dispose produced water into Formation B, J, K, D,M. Laboratory tests were performed to investigate theÂ effect of the injection of water into the reservoir formation. The experiment was conducted by measuringÂ water permeability as a function of fluid volume injection. In addition, XRD analysis was also performedÂ on effluent filtrate to support the results. Prior to investigating the sensitivity of reservoir rock to the fluidÂ injection, the samples were injected with fresh water, saline water, produced water collected from CentralÂ Injection Facility, and also Filtered CIF Water. The results indicated that all formations were sensitive toÂ fresh water and produced water. Moreover, the use of a filter will improve the water quality. Therefore,Â the produced water should be treated by using a filter and increasing water salinity. The XRD analysis showed that the potential damage is mostly caused by fine migration clay, however, swelling clay is also present in the small part of formation. The test results will be used for water treatment design, so as to minimize formation damage.